The effect of extended milking intervals (24, 48 and 72 h) on milk yield, milk composition, mammary physiology and welfare traits in dairy ewes. Issue 4 (8th November 2018) - Armaou, Evrydiki; Simitzis, Panagiotis; Koutsouli, Panagiota; Zoidou, Evagelia; Massouras, Theofilos; Goliomytis, Michael; Bizelis, Iosif; Politis, Ioannis
Abstract : The majority of the work today regarding the effects of extended milking intervals has focused on dairy cattle and only to a limited extent on dairy goats and sheep. The aim of this study was to investigate the effect of different non-milking intervals on milk yield and composition, mammary physiology and welfare indices in dairy ewes. Thirty-six multiparous ewes in late lactation were allocated to one of four groups of nine and subjected to 24, 48 or 72 h of non-milking or normal milking interval (12 h) (group A, B, C and D, respectively). Data showed that there were no significant differences in milk yield among the experimental groups during the third day after re-milking. Furthermore, no significant differences in milk lactose, protein and fat concentration among the experimental groups were observed after 7, 14 and 21 d of re-milking, respectively. Non-milking for 72 h resulted in a temporary increase of sodium concentration, Na + /K + ratio and enzymatic activities of plasmin (PL), plasminogen (PG) and plasminogen activator (PA) in milk. However, these parameters had similar values among the experimental groups on day 5 after re-milking. The concentration of lactose in blood was also significantly increased as a result of the 72 h non-milking interval and returned to its initial levels the second day after re-milking. These data, taken together, suggest that early involution events that occurred as an effect of non-milking were fully reversible within a short period of time. Finally, no significant signs of welfare impairment were observed in ewes due to extended milking intervals. In conclusion, non-milking up to 72 h had no negative effects on milk yield and composition, mammary physiology and welfare parameters in dairy ewes.